2021
DOI: 10.1590/1982-4327e3120
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Adjustment of Parents of Children with Different Cancer Prognoses

Abstract: Little is known about the psychological adjustment of parents of children with cancer relapse or remission. This study investigated differences in the psychological adjustment of caregivers of children with different cancer prognosis, by comparing them with a control group. In total, 183 caregivers participated in this study: those with children in relapse/on treatment (n = 32), remission/off treatment (n = 75), and “healthy” (n = 76). The Beck Depression and Anxiety Inventories, the Symptom Check list-90-R, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…One component of EFM was parental mutuality; this can be explained that even though the child experienced the worse conditions, if the parental mutuality were superior would cause the repair of children's HRQOL. A survey of 111 parents of children with cancer treatment in South Korea reported that family communication skills (ß = 0.403, p < 0.001) were a protective factor for family resilience as much as 29% [72,73]. Moreover, the better easy family management indicated families had various skills and knowledge in caring for their children in any conditions and could handle it well in case their child got severe disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One component of EFM was parental mutuality; this can be explained that even though the child experienced the worse conditions, if the parental mutuality were superior would cause the repair of children's HRQOL. A survey of 111 parents of children with cancer treatment in South Korea reported that family communication skills (ß = 0.403, p < 0.001) were a protective factor for family resilience as much as 29% [72,73]. Moreover, the better easy family management indicated families had various skills and knowledge in caring for their children in any conditions and could handle it well in case their child got severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mediating effect of DFM on the severity of disease and HRQoL can be explained that the coping of parents different individually, such as perception of their child's future and perceived di culty while taking care of their child potentially worse the child's HRQoL, as mentioned of a study of caregivers of childhood cancer during active treatment in Spain experienced less psychological adjustment than parents whose children had completed treatment [73]. Additionally, this nding was in line with a newest previous study that parents who had negative parenting styles had mediated the relationship between parental stress and behavioral problems of children [75]…”
Section: Discussionmentioning
confidence: 99%
“…Em outros dois artigos incluídos na revisão (8,9) , foi revelado que os pais expressaram receios sobre a recidiva do câncer após a conclusão do tratamento, e aqueles pais que já haviam passado pela recidiva relataram que tal experiência se mistura com a sensação de que todo o esforço feito no primeiro tratamento foi inútil, para além do medo sobre o futuro da criança, que causa sentimentos ligados à morte.…”
Section: Repercussões Da Recidiva Do Câncer Pediátrico Para Os Famili...unclassified
“…Outro artigo analisado (9) demonstrou que as crianças recidivadas sofrem com sintomas mais intensos do câncer, e que os pais de crianças menores apresentam mais ansiedade e problemas psicológicos do que aqueles com crianças maiores/adolescentes. Os cuidadores mais velhos e aqueles sem parceiro, com menor escolaridade e/ou rendimento, tenderam a apresentar mais ansiedade, depressão e sintomas mais graves e intensos.…”
Section: Repercussões Da Recidiva Do Câncer Pediátrico Para Os Famili...unclassified